(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The object of the study was the cooking liquor, spent liquor, the flow rate of washing water, their purification after washing, and the quality indicators of the cotton pulp obtained. We studied the optical density before and after bleaching with sodium hypochlorite (NaClO), experimentally determined the optimal bleaching rate of spent liquor and wash water, studied reducing the pH of the medium, determined the residual amount of sodium hydroxide, and identified the chemical oxygen demand (COD5) and biochemical oxygen demand (BOD5) waste liquor and wash water.